The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/pc.24151
|View full text |Cite
|
Sign up to set email alerts
|

Oat hull fibers bleached by reactive extrusion with alkaline hydrogen peroxide in thermoplastic starch/poly(butylene adipate‐co‐terephthalate) composites

Abstract: The bleaching of fibers using alkaline hydrogen peroxide (AHP) can be used to promote modifications aimed at enhancing their interactions with polymers in composites. Reactive extrusion with AHP (7 and 20 wt%, hulls basis), pH 11.5, was used to modify oat hull fibers. The fibers were further compounded with a thermoplastic starch/poly(butylene adipate‐co‐terephthalate) blend to form sheets. The bleaching influenced the color of the fibers and subsequently the color of the composites. The rougher surfaces obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…4 In this regard, the effect of chemical treatment on several natural fibers such as wheat straw, Munguba, oat hull, and Kenaf and their performance on the PBAT matrix has been previously reported. [5][6][7][8] The authors report increased fiber-matrix interaction by removing the lignin, hemicellulose, and hydroxyl groups from the fibers, which improves the stiffness, modulus of elasticity, and tensile and flexural strength of the PBAT matrix. Although chemical treatments have been successful in this type of fiber, environmental regulations motivate the exploration of other agro-industrial wastes and their green modification to develop biodegradable and environmentally friendly composites.…”
Section: Introductionmentioning
confidence: 99%
“…4 In this regard, the effect of chemical treatment on several natural fibers such as wheat straw, Munguba, oat hull, and Kenaf and their performance on the PBAT matrix has been previously reported. [5][6][7][8] The authors report increased fiber-matrix interaction by removing the lignin, hemicellulose, and hydroxyl groups from the fibers, which improves the stiffness, modulus of elasticity, and tensile and flexural strength of the PBAT matrix. Although chemical treatments have been successful in this type of fiber, environmental regulations motivate the exploration of other agro-industrial wastes and their green modification to develop biodegradable and environmentally friendly composites.…”
Section: Introductionmentioning
confidence: 99%
“…The above disadvantages severely hinder the application of PBAT as an agricultural film [ 12 ]. Studies have shown that UV light causes the main damage to plastic films [ 13 , 14 , 15 , 16 ]. To minimize the negative effects of UV light, the use of UV absorbers as additives has been put forward to prolong the durability of plastic products and has obtained significant results [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since starch is a biopolymer, its association with PBAT can even enhance environmental benefits. In fact, PBAT/starch blend has been used for the development of films with biodegradability and compostability properties, as an alternative to conventional non-biodegradable bags made of LDPE (Garcia et al, 2014(Garcia et al, , 2018Cardoso et al, 2018;Olivato et al, 2013Olivato et al, , 2014Brandelero et al, 2013;Nobrega et al, 2013).…”
Section: Introductionmentioning
confidence: 99%